Case report: Gastroenterological management in a case of cardio-facio-cutaneous syndrome - Ciacchini, B.; Di Nardo, G.; Marin, M.; Borali, E.; Caraccia, M.; Mogni, R.; Cairello, F.; Rabbone, I.; Ferrero, G. B; Pini Prato, A.; Felici, E. (Frontiers in Pediatrics, 2023)
ABSTRACT Background: cardio-facio-cutaneous syndrome is a rare genetic disorder affecting less 900 people in the world. It is mainly characterized by craniofacial, dermatologic and cardiac defects, but also gastroen-terological symptoms may be present, ranging from feeding difficulties to gastroesophageal reflux and constipation. In this report we describe a case of this syndrome characterized by severe feeding and growth difficul-ties, with a particular focus on the management of gastroenterological complications. Case presentation: the patient was a caucasian male affected by Cardio-Facio-Cutaneous syndrome who presented feeding difficulties already a few hours after birth. These symptoms worsened in the fol-lowing months and lead to a complete growth arrest and malnutrition. He was first treated with a naso-gastric tube placement. Subsequently, a laparoscopic Nissen fundoplication and a laparoscopic Stamm gastrostomy were performed. The child was fed with nocturnal enteral nutrition and diurnal oral and en-teral nutrition. Eventually the patient resumed feeding validly and regained adequate growth. Conclusion: this paper aims to bring to light a complex rare syndrome that infrequently comes to the at-tention of the pediatricians and whose diagnosis is not always straightforward. We also highlight the possible complications under a gastroenterologic point of view. Our contribution can be helpful to the pediatrician in the first diagnostic suspect of this syndrome. In particular, it is worth highlighting that -in an infant with Noonan-like features- symptoms like suction or swallowing problems, vomiting and feeding difficulties should orient towards the diagnosis of a Cardio-facio-cutaneous syndrome. It is also important to stress that its related gastroenterological issues may lead to severe growth failure and therefore the role of the gastroenterologist is key to manage supplemental feeding and to establish whether a naso-gastric or gastrostomic tube placement is necessary.